Extraction of stevioside and rebaudioside a from stevia rebaudiana by percolation with ethanol-water solvents - Celaya, Liliana Soledad (2022)
Fil: Celaya, Liliana Soledad. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales. Laboratorio Central; Argentina.